The 'other' side of memory: the survival of pro-regime memorialisation in democratic Chile (1990-2020) - Infante Batiste, V (2022)
The thesis investigates the conditions that explain the survival of pro-regime memorialisation in democratic Chile (1990 – 2020). A pro-regime memory site is a monument, memorial or symbolic marker (e.g., street name) built to celebrate a past authoritarian government. In Chile, these sites either praise the military coup of 11th of September 1973, glorify General Augusto Pinochet’s 17-year dictatorship (1973 – 1990), or celebrate Military Junta members and civil collaborators. Their survival – that is, their maintenance by authorities (city councils, judicial actors) – is a striking phenomenon in a context in which victims’ human rights memorials dominate the public space. To enhance the internal validity of the thesis, the elimination of pro-regime memorials is also investigated. The thesis elaborates a theoretical framework to explain the survival and elimination outcome, with four and five conditions, respectively. Using Qualitative Comparative Analysis (QCA), the research minimised the presence and absence of these conditions in a sample of 17 cases of pro-regime memorials. It obtained a parsimonious solution for both outcomes (survival and elimination). The QCA procedure uncovered that the survival of pro-regime memorialisation is explained by the presence of “Walls” (veto players), and a combination of “Silence” (absence of external intervention by NGOs and victims’ associations) and “Local and/or Institutional Support” (support towards the site’s survival by local communities and State institutions). Likewise, the elimination of pro-regime memorialisation is explained by the rejection of the site by the local community, or by a combination of civil society pressure and the presence of “Windows of Opportunity” (centre-left or left-wing city councils, or judges receptive to human rights). The results highlight the continued relevance of veto players in the survival of pro-regime memorialisation. The findings also emphasise the prominence of civil society, particularly local communities, in advancing both the survival and elimination of pro-regime memory sites in Chile.